Gestión presupuestaria del Gobierno Autónomo Descentralizado de la parroquia “La Esmeralda” Durante el periodo 2020-2021. - Luna Martínez, Betty Mariuxi (2022)
In the period 2020 - 2021 the economy was affected by the pandemic that was generated due to COVID-19, in the same way the financial sector of each country was affected and health protection was required, in the case of our country the Ministry of Economy and Finance was in charge of distributing the necessary funds for this situation, for which the Municipal and Parish GAD did not receive the corresponding budget as it has been in previous years, that is why in this case study it is proposed to analyze the management of the budget delivered to the Parish GAD of La Esmeralda belonging to the Montalvo canton to learn more about how the budget reduction was managed and how it affected the functions, planning and works that the GAD had planned to fulfill in the year.